Analyzing commercial bank in Indonesia by using camel method, case study of: pt bank mandiri (persero), tbk (bmri) for periods of 2007-2016) - Obrina Hutabarat, Vanessa Helena; Daryanto, Wiwiek M. (The Indonesian Journal of Business Administration, 2018)
Abstract – Assessment of bank’s soundness is fundamental since even a little macro-economic condition can influence customers trust on banks. Bank Mandiri expected by president of Indonesia to expanding their business in Southeast Asia, whereas they have some issues such as the rising of their non-performing loan and the decline of their profit and also in their credit quality. With all these issues, Bank Mandiri have to convince foreign market that they have a good trend of bank soundness and can be trusted. The purpose of this research is to assess bank soundness of Bank Mandiri from 2007-2016 and to find the priority ratios. In this research, CAMEL method that stands for Capital (C), Assets Quality (A), Management (M, Earning (E), and liquidity (L) is used for determining Bank Mandiri bank soundness for the last ten years. As for determine ratios that have strongest correlation, correlation statistic method will be used. Data used in this assessment are secondary data from Indonesia Stock Exhange. Those data are financial report and annual report from Bank Mandiri since 2007 until 2016.  The results showed that Bank Mandiri has healthy status based on CAMEL method. Other than that, also found that ratios that be the priority as early warning in Bank Mandiri based on CAMEL method is OER and ROA. Recommendation from this research is Bank Mandiri needs to take notice on movement of trend at NPL ratio, ROA, and LDR. Bank Mandiri also needs to maintain movement of OER in order to have optimal ROA. Keywords:  CAMEL, Correlation, Financial Ratio, Surat Edaran Bank Indonesia No. 6/23/DPNP/2004